The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1016/0379-0738(94)90333-6
|View full text |Cite
|
Sign up to set email alerts
|

Spleen findings in drowning

Abstract: A retrospective study of spleen findings in 42 victims of drowning and a comparison group of 42 c,lses of asphyxiation due to other causes (hanging, ligature strangulation and manual strangulation), that were matched for sex, age, body weight and build, was performed.Significantly smaller spleen weights (P < 0.05), spleen weightbody weight ratios (P < 0.01) and spl.een weight:liver weight ratios (P < 0.01) were found in the victims of drowning. The difference in weight was -18"!.,. A significant negative corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…In a series of 42 victims of freshwater drowning, the spleen weight was lower than in matched controls, with half the spleens being of a weight under the lower limit of controls (Haffner et al 1994). The value of the spleen weight as well as that of the weight ratio of the lungs and pleural effusion to the spleen, defined by some authors as the 'drowning index' , is questionable due to the wide variation of lung and spleen weight in the autopsy population.…”
Section: Spleenmentioning
confidence: 98%
“…In a series of 42 victims of freshwater drowning, the spleen weight was lower than in matched controls, with half the spleens being of a weight under the lower limit of controls (Haffner et al 1994). The value of the spleen weight as well as that of the weight ratio of the lungs and pleural effusion to the spleen, defined by some authors as the 'drowning index' , is questionable due to the wide variation of lung and spleen weight in the autopsy population.…”
Section: Spleenmentioning
confidence: 98%
“…This, he suggested, showed the spleen had contracted [2]. Observations of human splenic volume reduction have been recorded more recently [3][4][5][6][7]. A comprehensive series of in-vitro studies found that stimulation of the postganglionic sympathetic nerves to the human spleen evoked reductions in spleen volume [2].…”
Section: Discussionmentioning
confidence: 92%
“…All research on splenic volume reduction has been associated with sympathetic nervous system activity [1]. In these studies, the volume changes of the spleen were demonstrated by use of ultrasound [5], magnetic resonance imaging [6], or nuclear medicine [1]. Other studies used spleens obtained by surgery [2] or autopsy [4].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…217 suda boğulan, 166 pür asfiksi ve 381 travma ölümünde, akciğer, böbrek ve dalakta ortalama organ ağırlığının asfikside travmaya göre arttığı, hem asfiksi hem de suda boğulmada dalak ve karaciğer ağırlığının arttığı, suda boğulmada asfiksiye göre sadece akciğer ve böbreklerin ortalama ağırlığının arttığını belirtmişlerdir. Bazı çalışmalarda; ası, elle ya da bağla boğma gibi sebeplerden dolayı gelişen asfiksiler ile karşılaştırıldığında, dalak ağırlığı/vücut ağırlığı oranının suda boğulma kurbanlarındakinden önemli ölçüde daha küçük olduğu bulunmuştur (11,12). Bu deneysel çalışmada, suda boğulma olgularının organ ağırlıkları diğer asfiktik ölümlerle karşılaştırılmamış, ayrıca dalak ağırlığı çalışmaya dâhil edilmemiştir.…”
Section: Discussionunclassified